Globular adiponectin ameliorates metabolic insulin resistance via AMPK‐mediated restoration of microvascular insulin responses. (26th July 2015) - Zhao, Lina; Fu, Zhuo; Wu, Jing; Aylor, Kevin W.; Barrett, Eugene J.; Cao, Wenhong; Liu, Zhenqi
Abstract : Key points: Adiponectin is an adipokine with anti‐inflammatory and anti‐diabetic properties. Hypoadiponectinaemia is closely associated with endothelial dysfunction and insulin resistance in obesity and diabetes. Insulin resistance is present in muscle microvasculature and this may contribute to decreased insulin delivery to, and action in, muscle. In this study we examined whether adiponectin ameliorates metabolic insulin resistance by affecting muscle microvascular recruitment. We demonstrated that a high‐fat diet induces vascular adiponectin and insulin resistance but globular adiponectin administration can restore vascular insulin responses and improve insulin's metabolic action via an AMPK‐ and nitric oxide‐dependent mechanism. This suggests that globular adiponectin might have a therapeutic potential for improving insulin resistance and preventing cardiovascular complications in patients with diabetes via modulation of microvascular insulin responses. Abstract: Hypoadiponectinaemia is closely associated with endothelial dysfunction and insulin resistance, and microvasculature plays a critical role in the regulation of insulin action in muscle. Here we tested whether adiponectin replenishment could improve metabolic insulin sensitivity in male rats fed a high‐fat diet (HFD) via the modulation of microvascular insulin responses. Male Sprague–Dawley rats were fed either a HFD or low‐fat diet (LFD) for 4 weeks. Small resistance artery myograph changes in tension, muscle microvascular recruitment and metabolic response to insulin were determined. Compared with rats fed a LFD, HFD feeding abolished the vasodilatory actions of globular adiponectin (gAd) and insulin on pre‐constricted distal saphenous arteries. Pretreatment with gAd improved insulin responses in arterioles isolated from HFD rats, which was blocked by AMP‐activated protein kinase (AMPK) inhibition. Similarly, HFD abolished microvascular responses to either gAd or insulin and decreased insulin‐stimulated glucose disposal by ∼60%. However, supplementing gAd fully rescued insulin's microvascular action and significantly improved the metabolic responses to insulin in HFD male rats and these actions were abolished by inhibition of either AMPK or nitric oxide production. We conclude that HFD induces vascular adiponectin and insulin resistance but gAd administration can restore vascular insulin responses and improve insulin's metabolic action via an AMPK‐ and nitric oxide‐dependent mechanism in male rats. Abstract :